2005
DOI: 10.1038/436792a
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in a signalling pathway

Abstract: Protein kinases are enzymes that are important for controlling cellular growth and invasion, and their malfunction is implicated in the development of some tumours. We analysed human colorectal cancers for genetic mutations in 340 serine/threonine kinases and found mutations in eight genes, including in three members of the phosphatidylinositol-3-OH kinase (PI(3)K) pathway. The discovery of this mutational activation of a key cell-signalling pathway may provide new targets for therapeutic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
385
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 531 publications
(407 citation statements)
references
References 9 publications
20
385
0
2
Order By: Relevance
“…This gene is mutated in 15-30% of colorectal cancers, with hotspots identified in exons 1, 2, 9 and 20, and mutated p110a proteins have shown in vitro a gain of enzymatic function by activating the AKT signalling in the absence of growth factors and are thus oncogenic in cell culture and animal models (Samuels et al, 2004;Ikenoue et al, 2005;Kang et al, 2005). In colorectal cancer, PIK3CA mutations occur more frequently in women, and in the proximal part of the colon (Benvenuti et al, 2008;Barault et al, 2008b), a double mutation of the gene is observed in 6-9% of the mutated cases (Samuels et al, 2004;Barault et al, 2008b) and there is a significant concomitant occurrence of KRAS and PIK3CA mutations (Parsons et al, 2005;Velho et al, 2005;Barault et al, 2008b).…”
Section: Mapk Pathway Mutationsmentioning
confidence: 99%
“…This gene is mutated in 15-30% of colorectal cancers, with hotspots identified in exons 1, 2, 9 and 20, and mutated p110a proteins have shown in vitro a gain of enzymatic function by activating the AKT signalling in the absence of growth factors and are thus oncogenic in cell culture and animal models (Samuels et al, 2004;Ikenoue et al, 2005;Kang et al, 2005). In colorectal cancer, PIK3CA mutations occur more frequently in women, and in the proximal part of the colon (Benvenuti et al, 2008;Barault et al, 2008b), a double mutation of the gene is observed in 6-9% of the mutated cases (Samuels et al, 2004;Barault et al, 2008b) and there is a significant concomitant occurrence of KRAS and PIK3CA mutations (Parsons et al, 2005;Velho et al, 2005;Barault et al, 2008b).…”
Section: Mapk Pathway Mutationsmentioning
confidence: 99%
“…However, the AKT2 gene is amplified in about PTEN/PI3K signaling perturbations in cancer M Keniry and R Parsons 10% of ovarian cancers and 3% of breast cancers (Bellacosa et al, 1995;Parsons et al, 2005). A recent study has also reported that AKT1 is mutated within the Pleckstrin Homology Domain (E17K) in 8% of breast, 6% of colorectal and 2% of ovarian cancers that were examined (Carpten et al, 2007).…”
Section: Perturbations Of Pten Signaling In Cancermentioning
confidence: 99%
“…Different results indicate isoform-specific functions in tumor cells. For instance, mutations and amplifications in epithelial tumors have been detected mainly in Akt2 and very rarely in Akt1 (Bellacosa et al, 2004;Parsons et al, 2005). Overexpression of Akt2, but not Akt1, increased the invasiveness of a tumor breast cell line in vitro and in animal models (Arboleda et al, 2003).…”
Section: Introductionmentioning
confidence: 99%